miR-1, miR-133a, miR-29b and skeletal muscle fibrosis in chronic limb-threatening ischaemia - Alan J. Keane; Clara Sanz-Nogués; Dulan Jayasooriya; Michael Creane; Xizhe Chen; Caomhán J. Lyons; Isha Sikri; Katarzyna Goljanek-Whysall; Timothy O’Brien (Scientific Reports)
Abstract Chronic limb-threatening ischaemia (CLTI), the most severe manifestation of peripheral arterial disease (PAD), is associated with a poor prognosis and high amputation rates. Despite novel therapeutic approaches being investigated, no significant clinical benefits have been observed yet. Understanding the molecular pathways of skeletal muscle dysfunction in CLTI is crucial for designing successful treatments. This study aimed to identify miRNAs dysregulated in muscle biopsies from PAD cohorts. Using MIcroRNA ENrichment TURned NETwork (MIENTURNET) on a publicly accessible RNA-sequencing dataset of PAD cohorts, we identified a list of miRNAs that were over-represented among the upregulated differentially expressed genes (DEGs) in CLTI. Next, we validated the altered expression of these miRNAs and their targets in mice with hindlimb ischaemia (HLI). Our results showed a significant downregulation of miR-1, miR-133a, and miR-29b levels in the ischaemic limbs versus the contralateral non-ischaemic limb. A miRNA target protein-protein interaction network identified extracellular matrix components, including collagen-1a1, -3a1, and -4a1, fibronectin-1, fibrin-1, matrix metalloproteinase-2 and -14, and Sparc, which were upregulated in the ischaemic muscle of mice. This is the first study to identify miR-1, miR-133a, and miR-29b as potential contributors to fibrosis and vascular pathology in CLTI muscle, which supports their potential as novel therapeutic agents for this condition.